1. ## Another simplify question

Here's another please, does this make sense?

Question: 2(t + 6) - 3(4 - 3t)

= (t + 12) - (12 - 3t)
= t x 12 + t - 3t +12-12 + 12-3t
= 12t + 3t^2 + 0 + 9t
= 21t - 3t^2

That right? or miles off?

Cheers

Awesome! Thanks

Here's another then please, does this make sense?

Question: 2(t + 6) - 3(4 - 3t)

= (t + 12) - (12 - 3t)
= t x 12 + t - 3t +12-12 + 12-3t
= 12t + 3t^2 + 0 + 9t
= 21t - 3t^2

That right? or miles off?

Cheers

2(t+6) - 3(4 - 3t)

= (2t + 12) - (12 - 9t)

= 2t + 12 - 12 + 9t

= 2t + 9t

= 11t

=

EDIT: Well you edited something Mr F, why is there an extra equal sign?

Here's another please, does this make sense?

Question: 2(t + 6) - 3(4 - 3t)

= (t + 12) - (12 - 3t)
= t x 12 + t - 3t +12-12 + 12-3t
= 12t + 3t^2 + 0 + 9t
= 21t - 3t^2

That right? or miles off?

Cheers
The distributive law states you must multiply those outside the brackets by those inside

that being said;

2(t + 6) - 3(4 - 3t)
=2*t+2*6-3*4-3*(-3t)
=2t+12-12+9t
=2t+9t
=11t